Kerukunan Umat Beragama dalam Bingkai Iman Kristen di Era Disrupsi - Simon Simon; Yonatan Alex Arifianto (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The Indonesian nation is facing an era where horizontal conflicts often occur. Especially in the era of digital progress and the era of disruption that forces people to use technology to communicate, do business and so on. So that in the era of disruption, many hate speech accessed in cyberspace can threaten unity in the real world. By using a literature study approach, this paper intends to explain how Christians have an impact and become agents of truth through living in harmony and being pioneers in harmony. It was concluded that for Christians, harmony must also be done in a real place in the community as well as in the social media community which is now called the era of globalization in the era of disruption. Through the era of disruption and challenges, Christians can understand that any situation and condition still contributes to the diversity of the nation. It is also in line with the Basic Christian Faith in the harmony which can then be actualized by Christians in society in an era of disruption.